Positional proteomics reveals differences in N‐terminal proteoform stability - Daria Gawron; Elvis Ndah; Kris Gevaert; Petra Van Damme (Molecular Systems Biology)
Abstract To understand the impact of alternative translation initiation on a proteome, we performed a proteome‐wide study on protein turnover using positional proteomics and ribosome profiling to distinguish between N‐terminal proteoforms of individual genes. By combining pulsed SILAC with N‐terminal COFRADIC, we monitored the stability of 1,941 human N‐terminal proteoforms, including 147 N‐terminal proteoform pairs that originate from alternative translation initiation, alternative splicing or incomplete processing of the initiator methionine. N‐terminally truncated proteoforms were less abundant than canonical proteoforms and often displayed altered stabilities, likely attributed to individual protein characteristics, including intrinsic disorder, but independent of N‐terminal amino acid identity or truncation length. We discovered that the removal of initiator methionine by methionine aminopeptidases reduced the stability of processed proteoforms, while susceptibility for N‐terminal acetylation did not seem to influence protein turnover rates. Taken together, our findings reveal differences in protein stability between N‐terminal proteoforms and point to a role for alternative translation initiation and co‐translational initiator methionine removal, next to alternative splicing, in the overall regulation of proteome homeostasis.